Exploring MAP3K genes in gastric cancer: biomarkers, tumor microenvironment dynamics, and chemotherapy resistance - Senhui Wei; Ying Li; Jing Zhou; Yongming Xia (Hereditas)
Abstract Background Gastric cancer (GC) presents a significant global health burden, necessitating a deeper understanding of its molecular underpinnings for improved diagnostics and therapeutics. Methods In this study, we investigated the expression profiles and clinical implications of MAP3K genes in GC using in silico and in vitro experiments. Results Utilizing RT-qPCR analysis, we observed significant up-regulation of MAP3K1, MAP3K4, MAP3K5, MAP3K6, MAP3K7, MAP3K8, MAP3K9, and MAP3K10 in GC cell lines, while MAP3K2, MAP3K3, MAP3K11, MAP3K12, MAP3K13, MAP3K14, and MAP3K15 exhibited down-regulation. Prognostic evaluation revealed that elevated expression of MAP3K1, MAP3K4, MAP3K7, MAP3K8, MAP3K9, and MAP3K10 was associated with shorter overall survival (OS), emphasizing their clinical significance. Furthermore, the diagnostic potential was demonstrated through robust Receiver operating characteristics (ROC) curve analysis, indicating the strong discriminatory power of these genes in distinguishing GC patients. Proteomic analysis further confirmed the higher expression of MAP3K1, MAP3K4, MAP3K7, MAP3K8, MAP3K9, and MAP3K10 genes in GC. Methylation profiling further supported the idea that promoter hypomethylation of MAP3K1, MAP3K4, MAP3K7, MAP3K8, MAP3K9, and MAP3K10 genes was associated with their up-regulation. Single-cell functional analysis elucidated the involvement of MAP3K genes in shaping the tumor microenvironment. miRNA-mRNA network analysis revealed intricate regulatory mechanisms, with hsa-mir-200b-3p emerging as a key regulator. Finally, the MAP3K1 knockdown has shown significant impacts on the cellular behavior of the BGC823 cells. Conclusion This comprehensive assessment provides valuable insights into the role of MAP3K genes in GC, offering avenues for further research and therapeutic exploration.